Application of GIS in geoecological evaluation of terrain – case study nature park Hutovo blato - Hrelja, Edin; Drešković, Nusret; Korjenić, Aida; Sivac, Amina; Banda, Amra (Journal for Geography, 2021)
The subject of the research is the application of GIS in geoecological evaluation of terrain–case study Nature Park Hutovo blato. Geoecological evaluation of terrain is strongly relevant methodological procedure, which can be used for acquiring results about real value of particular areas. Method of terrain evaluation is also used, through five categories: hypsometric characteristics, angle of slopes, vertical dissection, terrain mobility and vegetation cover. The aim of the research is to clarify how valuable and useful certain segments of the terrain are for the purpose of spatial planning–for the tourism valorization, construction of various objects etc.Paper consists of several parts. First part defines the exact area of exploration. In the second part geomorphological characteristics of the researched area were analyzed. Geoecological evaluation of terrain, performed in third part was based onprevious geomorphological analysis as well as bonity categories. Methods used in this paper are: analysis, synthesis, statistical method and cartographic method. Complete analysis was conducted using GIS.